Flight-Log-Based Performance Analysis of a PID Controller for Pitch Response in a Quadcopter UAV - Akbar, Lalu Aan Sasaka; Bura, Romie Oktovianus; Mandaris , Dwi; Sahid, Ahmad; Widuri, Ani (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyzes the performance of an initial PID controller in the pitch channel of a quadcopter UAV using an empirical flight log exported from UAV Log Viewer. The aim is to evaluate pitch stability and command-following response by comparing desired pitch, current pitch, and North-East position data recorded during a 89.96s valid segment (2649 samples), analyzed through time-history inspection and error metrics. The method applies qualitative-quantitative log analysis with error metrics, time-history inspection, and trajectory interpretation. The results show weak pitch tracking: desired pitch varied from -1.34° to 4.14°, while measured pitch remained narrow at -0.73° to -0.50°; The log yielded MAE was 1.65°, RMSE was 2.04°, IAE = 148.46 degrees, and pitch correlation = 0.03.°. The findings imply that the initial gains are safe for data collection, but inadequate for responsive pitch control and require retuning.